Avaliação de biomarcadores de estresse oxidativo no diabetes mellitus gestacional - Rodrigues, Fabiane (2016)
Gestational diabetes mellitus (GDM) is a glucose intolerance beginning during pregnancy. It is a common disorder and its incidence is increasing among pregnant women. Hyperglycemia derived from GDM is associated with the formation of reactive oxygen species (ROS) in excess, which are capable of increasing oxidative stress and damage the health of both mother and fetus. The δ-aminolevulinate dehydratase enzyme (δ-ALA-D) is sensitive to oxidative conditions such as hyperglycemia. The aim of this study was to evaluate oxidative stress biomarkers in pregnant women with GDM and their relation to the activity of δ-ALA-D in order to analyze the oxidative profile of these pregnant women in the course of this disease. The evaluation was performed in 48 pregnant women with GDM and 30 healthy pregnant women (controls), both groups were in the third trimester. The activity of δ-ALA-D was measured in whole blood sample. Lipid peroxidation was evaluated by measuring thiobarbituric reactive substances (TBARS) in plasma and erythrocytes. Already for the analysis of antioxidant status were quantified levels of vitamin C (VIT C) in plasma, catalase (CAT) enzyme in erythrocytes, and the protein thiol groups (P-SH) in plasma and non-protein (NP-SH) in erythrocytes. The results showed a reduction of the δ-ALA-D activity, as well as an increase in its reactivation index in pregnant women with GDM compared to controls. Furthermore, there was an increase in TBARS levels in the GDM group (p<0.05). Antioxidants evaluated in pregnant women with GDM exhibited reduced levels compared to controls (p<0.05). In addition, there were significant correlations between δ-ALA-D and levels of NP-SH, reactivation index and erythrocyte TBARS; the latter was also correlated with fasting glucose levels in women with GDM. Therefore, there was an increase of oxidative stress in women with GDM, unlike what happens in a normoglycemic pregnancy. In parallel with increased oxidative stress was observed a reduction of the δ-ALA-D activity, which was shown to be sensitive to the hyperglycemic environment that emerged during pregnancy. Thus, the use of δ-ALA-D together with other markers of oxidative stress may be important to assess metabolic processes that are debilitated, as in GDM.